Characterization of Leptin (LEP) gene in Indian dromedary camel (Camelus dromedarius) - PRAKASH, VED; CHOUDHARY, NARENDRA; JYOTSANA, BASANTI; KUMAR JOSHI, RAJEEV; PANNU, URMILA (The Indian Journal of Animal Sciences, 2022)
Information on the camel leptin gene when compared to other domestic livestock species is very limited. Hence, the present study was undertaken to characterize the leptin gene of the Indian dromedary camel (Camelus dromedarius). Five overlapping primer pairs were designed utilizing the available Lama Glama leptin gene sequence. Through the assembly, alignment, and editing of the five overlapping nucleotide sequences, a 2425 bp long leptin gene sequence (Accession no. MT103545.1) of dromedary camel covering partial exon-2, intron-2, exon-3, and partial-3’ UTR region was characterized. The study successfully amplified the leptin gene, including intron-2 and 3’UTR of camel leptin gene for the first time using genomic DNA samples. The Indian dromedary camel leptin gene at the nucleotide level shared more than 97% similarity with llama and more than 80% similarity with major domesticated species like cattle, buffalo, sheep, and goat. The evolutionary relationship study based on amino acid sequences showed a close relationship between dromedary and bactrian camel species followed by llama. The high level of similarity between camel leptin gene amino acid sequence and other species showed the conserved nature of leptin protein.